The Transfer of Legal Philosophies: The Idea of Law in 19th Century - Trazegnies Granda, Fernando de (1980)
This preliminary work intends to explore the ways by which it is possible to approach a subject that constitutes the core of apparently diverse concerns but that can be organized from a common perspective: the transfer of legal systems. That is, the transplantation of a conception of law (and even, often, of a particular body of law) to a social reality different from the one that gave rise to it. By “system” we mean not only a given positive order, but more broadly the set of diverse elements, among which may be the positive order, but also convictions, social practices, etc., which are related to the legal and which in some way contribute to the fornation of a certain concept of law, of the perception of its functioning in a given society and of the role it is thought to have in such a society in terms of the realization of certain ends or values.